Metallisation and Interconnection of e-Beam Evaporated Polycrystalline Silicon Thin-Film Solar Cells on Glass - Taekyun Kim; Peter J. Gress; Sergey Varlamov (International Journal of Photoenergy)
One inherent advantage of thin-film technology is the possibility of using monolithic integration for series interconnection of individual cells within large-area modules. Polycrystalline silicon thin-film solar cells do not rely on transparent conducting oxide layers as the high sheet conductivity of the emitter and BSF layers enables the lateral flow of current from the film to the metal contacts. This paper presents a new method for the fabrication of e-beam evaporated polycrystalline thin-film photovoltaic minimodules on glass. The method involves electrically isolating minicells, by laser scribing, and then forming an isolation layer on each laser scribe. The main advantage of this metallisation is to have a single aluminium evaporation step for the formation of finger and busbar features, as well as for series interconnection.